2017
DOI: 10.1016/j.stemcr.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Enhances the Survival of Human Embryonic Stem Cells by Promoting DNA Repair

Abstract: SummaryHuman embryonic stem cells (hESCs) hold great promise for the treatment of many incurable diseases. Sirtuin1 (SIRT1), a class III histone deacetylase, is abundantly expressed in hESCs and is known to regulate early differentiation and telomere elongation. Here, we show that downregulation of SIRT1 promotes cell death in hESCs, but not in differentiated cells, and the SIRT1-inhibition-mediated cell death is preceded by increased DNA damage. This increased DNA damage is at least partially due to decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…MC-LR induces reproductive toxicity by being transported into testicular tissues and stimulating cell apoptosis by targeting the spermatogonia and Sertoli cells [ 41 ]. SIRT1 is a nicotinamide adenine dinucleotide (NAD+)-dependent class III histone deacetylase, and has important physiological roles in regulating cell survival, and protecting against apoptosis [ 42 ]. In this study, SIRT1 expression was inhibited both in MC-LR-treated Sertoli–germ cells and co-cultured cells obtained from rats treated with MC-LR for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…MC-LR induces reproductive toxicity by being transported into testicular tissues and stimulating cell apoptosis by targeting the spermatogonia and Sertoli cells [ 41 ]. SIRT1 is a nicotinamide adenine dinucleotide (NAD+)-dependent class III histone deacetylase, and has important physiological roles in regulating cell survival, and protecting against apoptosis [ 42 ]. In this study, SIRT1 expression was inhibited both in MC-LR-treated Sertoli–germ cells and co-cultured cells obtained from rats treated with MC-LR for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK is the mediator of cellular stress responses, involved in the phosphorylation of XRCC1 and regulation of oxidative stress response, promoting the damage repair [ 39 ]. Furthermore, SIRT represents a class of histone deacetylases, and downregulation of SIRT1 promotes cell death by decreasing DNA repair enzyme levels, including MSH2, MSH6, and APEX1 [ 40 ]. Cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…37 Jang et al found that SIRT1 inhibition increases DNA damage by reducing the level of DNA repair enzymes such as Apex1 and results in the activation of p53, leading to cell death through the activation of a number of genes involved in apoptosis. 38 This study showed that after 24 hours of treatment with YM155, the miR-9 expression levels increased significantly compared to control cells; in addition, the expression of two target genes, including MDR1 and SIRT1, decreased significantly. It is suggested that one of the effects of YM155 on inhibiting the growth and DNA damage response of leukemic cells can be via the miR-9/ SIRT1/p53 pathway ) Figure 4).…”
Section: Ym155 Increased Mir-9 and Decreased Survivin Bcl-2 And Genementioning
confidence: 73%